2017
DOI: 10.18632/oncotarget.v8i25
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The accessibility of chromatin is an essential feature of DNA templated processes such as DNA replication, transcription and DNA repair. The chromatin condensation state, and thus accessibility, is modulated by a variety of chromatin remodeling complexes [1] as well as epigenetic components; for instance by bridging gene regulatory elements [2]. More recently, the function of ncRNAs in regulating chromatin has received much attention. One important player that processes ncRNAs to control gene expression in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Indeed, ROS activates the NLRP3 inflammasome and has been associated with NeuroHIV (97,98). Another study found that inhibition of mTORC1 leads to decreased secreted IL-1b, indicating post-transcriptional effects on NLRP3 activation (94). A similar regulatory relationship was observed with in vitro and in vivo NLRP3 knock-out studies in which mTOR activity decreased (93,99).…”
Section: Hiv Induced Inflammasome Activation and Mtor Signaling In Ne...mentioning
confidence: 59%
See 1 more Smart Citation
“…Indeed, ROS activates the NLRP3 inflammasome and has been associated with NeuroHIV (97,98). Another study found that inhibition of mTORC1 leads to decreased secreted IL-1b, indicating post-transcriptional effects on NLRP3 activation (94). A similar regulatory relationship was observed with in vitro and in vivo NLRP3 knock-out studies in which mTOR activity decreased (93,99).…”
Section: Hiv Induced Inflammasome Activation and Mtor Signaling In Ne...mentioning
confidence: 59%
“…Although scarcely investigated, evidence of a regulatory relationships between mTOR and NLRP3 in immune cells and neurons have been reported. Studies have shown that downregulating mTOR activity reduces NLRP3 activation (93)(94)(95)(96). With reduced mTOR activity, autophagy removes detrimental proinflammatory stimuli, including ROS.…”
Section: Hiv Induced Inflammasome Activation and Mtor Signaling In Ne...mentioning
confidence: 99%
“…These effects were mediated by T-LAK cell-originated protein kinase (TOPK)-dependent enhancement of NF-kB transcriptional activity. In clinical samples, TLR4 and TOPK expression was significantly higher in high-grade breast cancer, invasive ductal carcinoma, and lymph node metastasis in comparison to low-grade samples and normal tissues (Seol et al, 2017). Other mechanisms were shown to mediate the LPS-induced breast cancer metastasis to other organs such as the prostaglandin E2-EP2 pathway (lung metastases) (Li et al, 2015) and the MYD88-leukotriene B 4 receptor-2 axis (small bowel metastases) (Park and Kim, 2015).…”
Section: Microbial-associated Molecular Patternsmentioning
confidence: 99%